EWS/FLI-responsive GGAA-microsatellites exhibit polymorphic differences between European and African populations - Beck, Robert (2012)
The genetics of Ewing sarcoma development remain obscure. The incidence of Ewing sarcoma is ten-fold less in Africans as compared to Europeans, irrespective of geographic location, suggesting population-specific genetic influences. Since GGAA-containing microsatellites within key target genes are necessary for Ewing sarcoma-specific EWS/FLI DNA binding and gene activation, and gene expression is positively correlated with the number of repeat motifs in the promoter/enhancer region, we sought to determine if significant polymorphisms exist between African and European populations which might contribute to observed differences in Ewing sarcoma incidence and outcomes. GGAA-microsatellites upstream of two critical EWS/FLI-target genes, NR0B1 and CAV1, were sequenced from subjects of European and African descent. While the characteristics of the CAV1 promoter microsatellites were similar across both populations, the NR0B1 microsatellite in African subjects was significantly larger, harboring more repeat motifs, a greater number of repeat segments, and longer consecutive repeats, than in European subjects. These results are biologically intriguing as NR0B1 was the most highly enriched EWS/FLI bound gene in prior studies, and is absolutely necessary for oncogenic transformation in Ewing sarcoma. These data suggest that GGAA-microsatellite polymorphisms in the NR0B1 gene might influence disease susceptibility and prognosis in Ewing sarcoma in unanticipated ways.